The Influence of Person-Job Fit and Leader-Member Exchange on Employee Performance with Self- Awareness as a Moderating Variable - Yuni Siswanti; Luthfia Dwi Listyaningrum; Sudaryati Sudaryati (Journal of International Conference Proceedings, 2025)
This research aims to determine, examine, and analyze the effect of person-job fit and leader- member exchange on employee performance moderated by self-awareness in civil servant employees at agency X in Yogyakarta, Indonesia. The population in this study was civil servant employees at agency X in Yogyakarta, Indonesia. The sampling technique for this study used exhaustive sampling, so that 87 people were obtained. Data collection was carried out by distributing questionnaires offline or in hard copy, then processed and analyzed using SEM PLS analysis with Smart PLS software. The results of this study indicate that: person-job fit has a significant effect on employee performance; leader- member exchange has a significant effect on employee performance; self-awareness is able to moderate the effect of person-job fit on employee performance; and self-awareness is able to moderate the effect of leader-member exchange on employee performance.